ANALISIS PATRIARKI PADA NOVEL CINTA SUCI ZAHRANA KARYA HABIBURAHMAN EL SHIRAZY - Purnamasari, Desi; Houtman, Houtman; Ardiansyah, Arif (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2023)
This study aims to describe and gain an in-depth understanding of analyzing patriarchy in the novel Holy Love Zahrana by Habiburahman El Shirazy. The focus of this study is patriarchy contained in the novel Holy Love Zahrana by Habiburahman El Shirazy with a subfocus on patriarchal forms and culture. This research is qualitative research with descriptive method. Keywords : Patriarchy, Zahrana's novel Holy Love.